Auditing cloud computing : a security and privacy guide - Halpert, Ben, 1986- (Hoboken, N.J. : John Wiley & Sons, 2011)
'The auditor's guide to ensuring correct security and privacy practices in a cloud computing environment. Many organizations are reporting or projecting a significant cost savings through the use of cloud computing--utilizing shared computing resources to provide ubiquitous access for organizations and end users. Just as many organizations, however, are expressing concern with security and privacy issues for their organization's data in the'cloud.' Auditing Cloud Computing provides necessary guidance to build a proper audit to ensure operational integrity and customer data protection, among other aspects, are addressed for cloud based resources. Provides necessary guidance to ensure auditors address security and privacy aspects that through a proper audit can provide a specified level of assurance for an organization's resources. Reveals effective methods for evaluating the security and privacy practices of cloud services. A cloud computing reference for auditors and IT security professionals, as well as those preparing for certification credentials, such as Certified Information Systems Auditor (CISA). Timely and practical, Auditing Cloud Computing expertly provides information to assist in preparing for an audit addressing cloud computing security and privacy for both businesses and cloud based service providers'--
Keywords: Business enterprises -- Computer networks -- Security measures; Cloud computing -- Security measures; Information technology -- Security measures; Data protection